Nd: YAG laser-induced hemorrhagic maculopathy - Kozak, Maciej; Pawlicka, Aleksandra; Sajak-Hydzik, Katarzyna; Hyjek-Ryś, Anna; Pawlicka, Ilona (Klinika Oczna / Acta Ophthalmologica Polonica, 2017)
Premacular hemorrhage in young adults is a rare, but turbulently and alarmingly manifested disease. The difficulty is to choose optimum treatment on a case-to-case basis. Fortunately, the prognosis is usually favorable. Whereas many causes of the condition have been known and described, a new group of patients is emerging, who do not meet the previously described criteria, yet labelling them as “idiopathic” would be an oversimplification. Here, we present a case of a patient treated in our hospital due to premacular hemorrhage which developed following an exposure to a Nd: YAG laser used at the disco.